True Interindividual Variability Exists in Postprandial Appetite Responses in Healthy Men But Is Not Moderated by the FTO Genotype. Issue 7 (27th May 2019) - Goltz, Fernanda R; Thackray, Alice E; Atkinson, Greg; Lolli, Lorenzo; King, James A; Dorling, James L; Dowejko, Monika; Mastana, Sarabjit; Stensel, David J
ABSTRACT: Background: After meal ingestion, a series of coordinated hormone responses occur concomitantly with changes in perceived appetite. It is not known whether interindividual variability in appetite exists in response to a meal. Objectives: The aim of this study was to 1 ) assess the reproducibility of appetite responses to a meal; 2 ) quantify individual differences in responses; and 3 ) explore any moderating influence of the fat mass and obesity associated ( FTO ) gene. Methods: Using a replicated crossover design, 18 healthy men (mean ± SD age: 28.5 ± 9.8 y; BMI: 27.0 ± 5.0 kg/m 2 ) recruited according to FTO genotype (9 AA, 9 TT) completed 2 identical control and 2 identical standardized meal conditions (5025 kJ) in randomized sequences. Perceived appetite and plasma acylated ghrelin, total peptide YY (PYY), insulin, and glucose concentrations were measured before and after interventions as primary outcomes. Interindividual differences were explored using Pearson's product-moment correlations between the first and second replicates of the control-adjusted meal response. Within-participant covariate-adjusted linear mixed models were used to quantify participant-by-condition and genotype-by-condition interactions. Results: The meal suppressed acylated ghrelin and appetite perceptions [standardized effect size (ES): 0.18–4.26] and elevated total PYY, insulin, and glucose (ES: 1.96–21.60). For all variables, SD of change scores was greater in the meal than in the control conditions. Moderate-to-large positive correlations were observed between the 2 replicates of control-adjusted meal responses for all variables ( r = 0.44–0.86, P ≤ 0.070). Participant-by-condition interactions were present for all variables ( P ≤ 0.056). FTO genotype-by-condition interactions were nonsignificant ( P ≥ 0.19) and treatment effect differences between genotype groups were small (ES ≤ 0.27) for all appetite parameters. Conclusions: Reproducibility of postprandial appetite responses is generally good. True interindividual variability is present beyond any random within-subject variation in healthy men but we detected no moderation by the FTO genotype. These findings highlight the importance of exploring individual differences in appetite for the prevention and treatment of obesity. This trial was registered at clinicaltrials.gov as NCT03771690.